From One Crisis to the Other: History and Literature in The Crisis from 1910 to the Early 1920s - Lamia Dzanouni; Hélène Le Dantec-Lowry; Claire Parfait (European Journal of American Studies)
This essay investigates the role of literature and the links between literature, news-reporting, and history in the NAACP magazine The Crisis between 1910 and the early 1920s. We do not study literature per se and do not provide an analysis of the literary style, nor do we assess the literariness of the short stories and poems printed in the 1910s. Rather, we examine the place accorded literature in the Crisis and its role in relation to the rest of the magazine, from news commentary, political essays, and echoes of the African past, to illustrations and advertisements.